Cu(I)-catalyzed direct addition and asymmetric addition of terminal alkynes to imines - Wei, Chunmei (National Academy of Sciences, 2004)
A Cu(I)-catalyzed direct addition of alkynes to imines was developed. The process is simple and provides a diverse range of propargylamines in high enantiomeric excess and good yield both in water and in toluene. The absolute configuration of such addition products has been determined by x-ray crystallography.